Robust asynchronous switching predictive control for multi-phase batch processes with time-varying tracking trajectory and delay. Issue 3 (4th March 2023) - Peng, Bo; Shi, Huiyuan; Su, Chengli; Wen, Xin; Li, Ping
Abstract : To solve the delay condition of the controller during adjacent phases and the change of the set value in multi-phase batch processes, a robust asynchronous switching predictive control scheme is proposed based on the mode-dependent average dwell time method. Firstly, the model of multi-phase batch processes including stable and unstable subsystems is established. Secondly, the LMI conditions to ensure that the system is asymptotically stable at each phase and exponentially stable at each batch are given. By solving these LMI conditions, not only the control law can be calculated, but also the shortest running time in the stable subsystems and the longest running time in the unstable subsystems can be obtained. Finally, according to these times, the controller is switched ahead of time to avoid the appearance of unstable subsystems. The comparison results of the injection moulding processes with the existing switching methods verifies the feasibility of the proposed method.